Plasma reactors with nanosecond coronas and semiconductor SOS generators; The 27th IEEE International Conference on Plasma Science, New Orleans, LA, june 4-7, 2000 - Mesyats G. A. Gennady Andreyevich (2000, 2000)
В фонде НТБ ТПУ отсутствует